ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KINERJA KARYAWAN DENGAN WORK FROM HOME SEBAGAI VARIABEL MODERASI - candra, rio; irfany, brenda; septyano, dihin (Awatara Publisher, 2023)
The purpose of this study was to examine the effects of work motivation, job satisfaction, and work discipline on employee performance at PT. Bank Mayapada International during the Covid-19 pandemic using Work From Home as a moderating variable. The population in this study were employees of PT. Bank Mayapada International's head office and a sample of 100 operational staff respondents who worked from home. The data for this study was collected using an online questionnaire. The scale used is a Likert scale with 25 statements. The analysis technique used is multiple linear regression and moderation regression. The results showed that: work motivation has an impact on employee performance, job satisfaction has an impact on employee performance, work from home has an impact on employee performance, work from home has effect of strengthening the relationship between work motivation and employee performance, work from home has effect of decreasing the relationship between job satisfaction and employee performance, work from home has effect of decreasing the relationship between work discipline and employee performance, and work motivation, job satisfaction, work discipline, and work from all affect employee performance all at the same time. The study's limitation is that it only used a sample of 100 operational staff respondents, whereas other divisions use a work from home system. Suggestions for future researchers also use variables other than work from home as moderating variables, as well as researching companies in other fields and increasing the number of samples to ensure more accurate research results. Keywords: Work Motivation, Job Satisfaction, Work Discipline, Work From Home And Employee Performance.